2018
DOI: 10.3897/zookeys.792.27255
|View full text |Cite
|
Sign up to set email alerts
|

Description and molecular analysis of Tylencholaimus helanensis sp. n. from China (Dorylaimida, Tylencholaimidea)

Abstract: A new species, Tylencholaimushelanensissp. n., extracted from the rhizosphere soil of unidentified grasses from Helan Mountain, Inner Mongolia, China was identified. The new species is characterized by having a body length of 0.93–1.07 mm with the lip region approximately one-quarter of the body diameter at the posterior end of the neck region wide; female didelphic-amphidelphic; pars proximalis vaginae violin-shaped. Males were not found. SEM observations of the new species were made and a phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, Tylencholaimus zhongshanensis sp. nov. can be differentiated from T. helanensis mainly by body length and shorter odontostyle (473–605 µm vs. 0.93–1.07 mm; 5–6 µm vs. 8–9.5 µm), and female prodelphic (vs. didelphic-amphidelphic) (Wu et al, 2018) although the sequences showed the highest similarity to each other.…”
Section: Resultsmentioning
confidence: 99%
“…However, Tylencholaimus zhongshanensis sp. nov. can be differentiated from T. helanensis mainly by body length and shorter odontostyle (473–605 µm vs. 0.93–1.07 mm; 5–6 µm vs. 8–9.5 µm), and female prodelphic (vs. didelphic-amphidelphic) (Wu et al, 2018) although the sequences showed the highest similarity to each other.…”
Section: Resultsmentioning
confidence: 99%
“…The presently reported populations represented five known species (T. mirabilis, T. teres, T. micronanus, T. ibericus and T. cosmos) and five new species. With the addition of the presently described new species, the total number of valid species under this genus is raised to 62 (Ahad & Ahmad 2016;Wu et al 2018;Golhasan et al 2019), 27 of them are recorded from India, and 11 species are recorded from the Western Ghats. Tylencholaimus mirabilis, the type species is reported here for the first time from India.…”
Section: Discussionmentioning
confidence: 99%